An aptamer and functionalized nanoparticle-based strip biosensor for on-site detection of kanamycin in food samples. Issue 1 (23rd November 2017) - Liu, Jing; Zeng, Jingyi; Tian, Yaping; Zhou, Nandi
Abstract : An aptamer and functionalized nanoparticle-based strip biosensor for highly sensitive and highly specific on-site detection of kanamycin in food samples. Abstract : A lateral flow strip biosensor for fast, sensitive, low-cost and on-site detection of kanamycin was developed by using kanamycin-specific aptamer-modified gold nanoparticles (AuNPs-apt) as a probe and oligonucleotide DNA1-modified silver nanoparticles (AgNPs-DNA1) as a signal amplification element. Through the complementary sequences of DNA1 and the aptamer, the AgNP-DNA1-apt-AuNPs complex can be formed and further captured on the test zone of the strip, where a capture probe DNA2 complementary to the 3′-terminal of DNA1 was immobilized. In the presence of kanamycin, it can competitively bind to the aptamer, and then inhibit the formation of the complex and the accumulation of AuNPs on the test zone. AuNPs-apt can finally be captured on the control zone via the specific binding between biotin and streptavidin. The assay avoids multiple incubation and washing steps and can be completed within 10 min. By observing the color change of the test zone, a qualitative detection for kanamycin can be achieved by the naked eye, with the visual limit of 35 nM. Meanwhile, a linear detection range of 1–30 nM with a low detection limit of 0.0778 nM for quantitative analysis can be achieved by using a scanning reader. The lateral flow strip biosensor exhibited high specificity and stability. Moreover, it was applied to detect kanamycin in various food samples, indicating its great potential in field testing.